Sun protection behavior of agricultural workers and associated factors in West of Turkey - Ozkan, Merve; Adana, Filiz; Yesilfidan, Duygu (Journal of the Pakistan Medical Association, 2022)
Objective: To determine sun-protection behaviours and related factors of agricultural workers in western Turkey. Method: The cross-sectional, analytical study was conducted from January to October 2019 in Aydn province Turkey after approval from the ethics review committee of the Aydin Adnan Menderes University Aydin. The study sample comprised agricultural workers of either gender. Data was collected using the Sun Protection Behaviour Scale. Data was analysed using SPSS 21. Results: Of the 254 subjects, 127(50%) each were males and females. Mean overall Sun Protection Behaviour Scale score was 20.29±5.61 and there was no significant differences in terms of gender, marital status and socioeconomic stratification (p>0.05). Sun Avoidance and Sunscreen Use subscale scores were high for female workers, while Hat Use behaviour score was high for the males (p<0.05). . Conclusion: The sun-protection level of agricultural workers was not found to be sufficient, with males, those with sunburn, and those having no knowledge about skin cancer showing more risky behaviours. Key Words: Agriculture, Workers, Sun, Behaviour, Turkey, Health.